Diagnosis and Treatment of Neurological and Ischemic Disorders Employing Carbon Nanotube Technology. (26th October 2016) - Komane, Patrick P.; Choonara, Yahya E.; du Toit, Lisa C.; Kumar, Pradeep; Kondiah, Pierre P. D.; Modi, Girish; Pillay, Viness
Abstract : Extensive research on carbon nanotubes has been conducted due to their excellent physicochemical properties. Based on their outstanding physicochemical properties, carbon nanotubes have the potential to be employed as theranostic tools for neurological pathologies such as Alzheimer's disease and Parkinson's disease including ischemic stroke diagnosis and treatment. Stroke is currently regarded as the third root cause of death and the leading source of immobility around the globe. The development and improvement of efficient and effective procedures for central nervous system disease diagnosis and treatment is necessitated. The main aim of this review is to discuss the application of nanotechnology, specifically carbon nanotubes, to the diagnosis and treatment of neurological disorders with an emphasis on ischemic stroke. Areas covered include the conventional current diagnosis and treatment of neurological disorders, as well as a critical review of the application of carbon nanotubes in the diagnosis and treatment of ischemic stroke, covering areas such as functionalization of carbon nanotubes and carbon nanotube-based biosensors. A broad perspective on carbon nanotube stimuli-responsiveness, carbon nanotube toxicity, and commercially available carbon nanotubes is provided. Potential future studies employing carbon nanotubes have been discussed, evaluating their extent of advancement in the diagnosis and treatment of neurological and ischemic disorders.